Possible rapid strain accumulation rates near cali, colombia, determined from gps measurements (1996-2003) (2004)
Global Positioning System (GPS) data from southern Central America and northwestern South America collected between 1991 and 1998 reveal wide plate margin deformation along a 1400 km length of the North Andes. Also associated with the oblique subduction of the Nazca plate at the Colombia-Ecuador trench is the 'escape' of the North Andes block (NAB). The NAB is delineated by the Bocono-East Andean fault systems and the Dolores Guayaquil Megasheare to the east, the South Caribbean deformed belt on the north and the Colombia-Ecuador trench and Panama on the west. Within the NAB many damaging crustal earthquakes have occurred which is most recently exemplified on January 25, 1999 (Mw = 6.1) Armenia earthquake. Preliminary analysis of recent occupations (2003 GEORED GPS) of several previously observed (1996-2001) GPS sites suggest shear strain accumulation rates in the Cauca valley near Cali of approximately 2.1 x 10-7 yr-1 and 1.6 x 10-7 yr-1. These strain rates are measured within 2 Delaunay triangles with common vertices at Cali and Restrepo, which encompass areas, located north and west of Cali.Seismicity has been monitored in the Cauca Valley for the last 17 years by the "Observatorio Sismológico del Suroccidente" (OSSO) since 1987 and by the Red Sismológica Nacional del INGEOMINAS since 1993. Their catalogs list numerous shallow earthquakes near Cali but nothing larger than magnitude 5. Historically, however, several large earthquakes are associated with the "Falla Cauca Almaguer" in locations both to the south and north of Cali in the Cauca valley. Preliminary calculations using the strain rates determined for these Delaunay triangles and a simplified Kostrov formula suggest possible decadal (30 - 90 years) recurrence intervals for Mw = 6.0 - 6.3 earthquakes, centenary (90 - 900 years) recurrence intervals for Mw = 6.4 - 6.9 earthquakes and millennial (900+ years) recurrence intervals for Mw ≥ 7 earthquakes.